The evaluation of the clinical and radiographic records of the first molar teeth in pediatric patients (Annals of Medical Research, 2021)
Aim: This study aimed to determine the status, the need for treatment, and the performed treatments in the first permanent molars, together with the general health status, in pediatric patients. Material and Methods: A total of 5996 teeth from 1499 children were included in the study. The first permanent molars were evaluated by panoramic radiography and patient recording system. The teeth were classified according to the following data: age, gender, jaw, side, teeth requiring therapy, preventive and interventional implementations.Results: It was determined that 45.7% of the first permanent molars were healthy and 54.3% were necessitating treatment. The rate of the healthy teeth was determined to decrease with increasing age (p0.001). The rate of healthy teeth in boys was higher than girls and the healthy teeth in maxilla were higher than mandible (p0.001). Applications for preventive treatment were most frequently performed between group 1 (p0.001). Preventive treatments were performed higher in boys than girls (p0.001). Mean age of first restorative treatment, endodontic treatment and extraction on first permanent molars were 10 years 7 months 18 days, 11 years 1 month 8 days and 11 years 5 months 13 days, respectively.Conclusion: Since the awareness of the families on the first permanent molars, which are among the first erupted permanent teeth, is low, and the oral hygiene of children is inadequate, caries and tooth loss are encountered very frequently in these teeth. In spite of developing dentistry technologies and ease of access, dental health is very dramatic in developing countries.
Keywords: First permanent molar; caries; dental treatment; preventive treatment.